A Proteolytic Complex Targets Multiple Cell Wall Hydrolases in Pseudomonas aeruginosa - Disha Srivastava (American Society for Microbiology, 2018)
ABSTRACT Carboxy-terminal processing proteases (CTPs) occur in all three domains of life. In bacteria, some of them have been associated with virulence. However, the precise roles of bacterial CTPs are poorly understood, and few direct proteolytic substrates have been identified. One bacterial CTP is the CtpA protease of Pseudomonas aeruginosa, which is required for type III secretion system (T3SS) function and for virulence in a mouse model of acute pneumonia. Here, we have investigated the function of CtpA in P. aeruginosa and identified some of the proteins it cleaves. We discovered that CtpA forms a complex with a previously uncharacterized protein, which we have named LbcA (lipoprotein binding partner of CtpA). LbcA is required for CtpA activity in vivo and promotes its activity in vitro. We have also identified four proteolytic substrates of CtpA, all of which are uncharacterized proteins predicted to cleave the peptide cross-links within peptidoglycan. Consistent with this, a ctpA null mutant was found to have fewer peptidoglycan cross-links than the wild type and grew slowly in salt-free medium. Intriguingly, the accumulation of just one of the CtpA substrates was required for some ΔctpA mutant phenotypes, including the defective T3SS. We propose that LbcA-CtpA is a proteolytic complex in the P. aeruginosa cell envelope, which controls the activity of several peptidoglycan cross-link hydrolases by degrading them. Furthermore, based on these and other findings, we suggest that many bacterial CTPs might be similarly controlled by partner proteins as part of a widespread mechanism to control peptidoglycan hydrolase activity. IMPORTANCE Bacterial carboxy-terminal processing proteases (CTPs) are widely conserved and have been associated with the virulence of several species. However, their roles are poorly understood, and few direct substrates have been identified in any species. Pseudomonas aeruginosa is an important human pathogen in which one CTP, known as CtpA, is required for type III secretion system function and for virulence. This work provides an important advance by showing that CtpA works with a previously uncharacterized binding partner to degrade four substrates. These substrates are all predicted to hydrolyze peptidoglycan cross-links, suggesting that the CtpA complex is an important control mechanism for peptidoglycan hydrolysis. This is likely to emerge as a widespread mechanism used by diverse bacteria to control some of their peptidoglycan hydrolases. This is significant, given the links between CTPs and virulence in several pathogens and the importance of peptidoglycan remodeling to almost all bacterial cells.